Green Products Strategy Impact Of Generic Porter Strategy On Company’s Performance - Saputra, Asep Rokhyadi Permana; Haryono, Tulus; Untoro, Wisnu (International Review of Management and Marketing, 2019)
The strategy is now essential for a company, especially in the dynamic era as it is today. A good strategy is needed to overcome the business issues, but it must also prioritize environmental factors. The strategy used in this study was adopted from generic porter strategy. As we know this strategy has been widely used by many companies in the world for 3.5decades.On the other hand, any strategy must also always consider the environment to be a green product that is friendly to the environment. The aims of this study is to, first, how the influence of porter generic strategy on firm performance, second, how the green products strategy reinforces the influence of porter generic strategy (differentiation and cost leadership) on the company’s performance. The method used in this study to answer the first objective was with Multiple Regression Analysis (MRA). Meanwhile, to answer the second objective, we used Moderated Multiple Regression (MMR). This study was conducted on companies that have been certified EIA (Environmental Impact Assessment) in the province of Daerah Istimewa Yogyakarta and Central Java with 264 of the 723 respondent companies (respond rate of 34.025%). The results showed that there’s influence between porter generic strategies with the company’s performance. These studies also showed that the Green Products Strategy may strengthen the influence of positive differentiation strategy on company performance, while the Green products strategy did not strengthen and positively influence the cost leadership strategy on Corporate Performance. Keywords: Generic Porter Strategy, Differentiation Strategy, Cost Leadership Strategy, Green Products Strategy. JEL Classifications: M31, Q5 DOI: https://doi.org/10.32479/irmm.7170